The country mail is coming : poems from down under - Fatchen, Max.; O'Neill, Catharine (Boston : Joy Street Books, 1990)
In this collection of poems, the author relates his experiences growing up in the Australian countryside.
Wilson's Children
School Library Journal
Booklist
5.1
3-6
Keywords: Country life -- Juvenile poetry; Children's poetry, Australian; Country life -- Poetry; Australian poetry; Country life -- Poetry; Australian poetry